FACTORS AFFECTING TAX COMPLIANCE AMONG SMALL BUSINESS ENTERPRISES: EVIDENCE FROM POKHARA VALLEY - Hari Bahadur Bhandari; Gokul Dhungana; Sayyida Sayyida (Fakultas Ekonomi dan Bisnis, Universitas Wiraraja Madura, 2025)
Taxes are levied in almost every country, primarily to raise revenue for government expenditures. Tax compliance issue is a major problem in revenue generation by the government in Nepal. This study therefore aims to examine the impact of tax knowledge and awareness, detection and punishment, tax system and implementation, attitudes towards tax, tax rewards and incentives, and tax policy on tax compliance behavior of small-sized enterprises of Pokhara Valley. The study is based on descriptive and analytical research design with a quantitative nature of data. Required data were collected through primary sources by using a self-administered questionnaire, coded, and analyzed by employing both descriptive and inferential statistics namely mean, standard deviation, Pearson’s correlation, and multiple linear regression models side by side 50 samples were selected along with a convenience sampling design. The study result confirms that the variables including tax knowledge and awareness, tax system and implementation, detection and punishment, and tax policy display low positive relationships with tax compliance behaviour but attitudes toward tax show a negative correlation. Besides this, the relationship between tax rewards and incentives and tax compliance behaviour is moderate. Additionally, all the explanatory variables have an insignificant impact on the tax compliance of the small-sized businesses of Pokhara Valley. It is anticipated that this study will offer significant new information and comprehension to academics, practitioners, policymakers, and other regulatory bodies involved in the creation of tax policies.